Identifying successful strategies for honey value chains in Brazil: a conjoint study. Issue 7 (4th July 2016) - Figueiredo Junior, Hugo Santana De; Meuwissen, Miranda P. M.; Van der Lans, Ivo A.; Oude Lansink, Alfons G. J. M.
Abstract : Purpose: Development studies rarely measure the impact of value chain strategies on performance. This paper quantifies the perceived contribution of strategies to the performance of three honey value chains in Brazil. Design/methodology/approach: The value chain Structure-Conduct-Performance (SCP) framework was used to select strategies and two performance indicators, honey production growth and local value-added. In a conjoint study, experts were asked to judge the contribution to the two performance indicators of several hypothetical combinations of value chain strategies. Findings: According to the experts, adoption of specialised technical assistance, sharing resources at the production step, increase in exports, and organic certification were the strategies which contributed the most to performance. Simulations suggested that some honey value chains could have greatly increased their performance with these higher pay-off strategies. Research limitations/implications: Quantifying the perceived impact of individual strategies contributes to improved evaluation of development interventions. Practical implications: Outcomes also show that conjoint analysis is a useful method for policy evaluations in data scarce situations. Originality/value: The paper combines an extended Structure-Conduct-Performance (SCP) framework for strategy selection and conjoint analysis for strategy evaluation of value chains.